Preparation and Mechanical Characterization of TiC Particles Reinforced Al7075 Alloy Composites - S. Krishna Prasad; Samuel Dayanand; M. Rajesh; Madeva Nagaral; V. Auradi; Rabin Selvaraj (Advances in Materials Science and Engineering)
The current exploration work focuses on the fabrication of aluminum 7075 matrix composites built up with different weight levels of titanium carbide particles by a traditional stir casting process. In particular, the combination of high hardness and flexible modulus, low density, great wettability, and low synthetic reactivity with aluminum melt makes TiC particle an attractive material. From 0% to 6 wt.% of reinforcement is introduced in steps of 3 wt.%. Aluminum matrix composites are studied in depth to learn more about their microstructures and mechanical properties. TiC particles were uniformly dispersed in the aluminum lattice, as shown by scanning electron micrographs of the material’s microstructure. As the weight of the TiC particles in the aluminum lattice increases, so does the density of the composites. The X-ray diffraction technique has also been used to detect the phase of TiC particles. As the amount of TiC particles in the aluminum matrix increases, the material’s mechanical properties, such as ultimate tensile strength and hardness, increase at the expense of ductility. The preorganized composites have also undergone fractography testing.